1981
DOI: 10.1016/0026-2862(81)90019-4
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum staining of coronary microvascular endothelium: Effects of ischemia reperfusion, propranolol, and atenolol

Abstract: Cat isolated hearts were perfused via the aorta with normothermic arterial blood from donor cats. After 1 hr of equilibration, dl-propranolol (1.9 mg/kg), atenolol (1.65 mg/kg), or physiological saline solution was infused via the aortic cannula. The hearts were made globally ischemic for 1 hr and reperfused for 1 hr. Hearts given saline but not made ischemic, and hearts from blood-donor cats served as controls. The hearts were flushed with physiological saline for 2 min, then perfused with cacodylate-buffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It is clear that one of the primary manifestations of reperfusion injury is microvascular dysfunction, which is centered largely on the endothelial cell (8,12). Microvascular dysfunction includes increased permeability, cell swelling, increased expression of endothelial adhesion molecules, increased leukocyte adhesion (1,8,12), and disruption of the glycocalyx (5,17,28). While the molecular causes of the dysfunction are not clear, previous work in this laboratory has shown that the glycocalyx is a dynamic structure that can respond rapidly to a number of stimuli, including production of reactive oxygen species (49) and TNF-␣ (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is clear that one of the primary manifestations of reperfusion injury is microvascular dysfunction, which is centered largely on the endothelial cell (8,12). Microvascular dysfunction includes increased permeability, cell swelling, increased expression of endothelial adhesion molecules, increased leukocyte adhesion (1,8,12), and disruption of the glycocalyx (5,17,28). While the molecular causes of the dysfunction are not clear, previous work in this laboratory has shown that the glycocalyx is a dynamic structure that can respond rapidly to a number of stimuli, including production of reactive oxygen species (49) and TNF-␣ (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using electron microscopy have shown that I/R injury causes significant damage to the endothelial glycocalyx (5,17,28). One of these studies found that the glycocalyx was entirely removed from the endothelium after 1 h of ischemia and 1 h of reperfusion (28) of feline coronary capillaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon completion of the designated protocol, hearts were perfused for 3 min with 2.5% glutaraldehyde and 1% LaCl 3 in 0.1 M sodium cacodylate buffer (pH 7.44). The electron-dense LaCl 3 serves as an indicator of blood vessel integrity (Haack et al, 1981). Tissue samples from the left ventricular myocardium immediately below the site of occlusion were cut into segments measuring approximately 1 mm on a side.…”
Section: Methodsmentioning
confidence: 99%